Investing in artificial intelligence applications in teaching English at the primary level - Aljurijeer, Shamma Sulimsn (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to review the literature from previous studies and research in the field of investing in artificial intelligence applications in teaching the English language, and to clarify the applications of artificial intelligence in the field of teaching the English language during the stages of lesson implementation (planning, implementation, evaluation). The researcher relied on the descriptive investigative approach in researching secondary sources from previous Arab and foreign books, studies and research, and used digital databases as tools for the study. The most important results and recommendations of the study are the following: All the results of previous studies confirmed the importance of using artificial intelligence in improving the level of achievement of learners, including primary school students. Artificial intelligence applications contributed to improving English language skills, listening, speaking, reading and writing. The most widespread applications are for the lesson evaluation stage. There are many websites and software through which students' level in the English language is evaluated, and evaluation methods that rely on artificial intelligence measure higher-order thinking skills, address cognitive performance, and work to evaluate cooperative and individual intelligence. The study recommended improving the cognitive awareness of English language teachers about the concept of artificial intelligence and its modern applications and how to invest in teaching the English language and its skills and providing specialized training packages on the use of educational robots and the virtual world environment in the educational process.
Keywords: Investment in intelligence applications; Learning English; Primary stage